2015
DOI: 10.18488/journal.66/2015.2.1/66.1.17.33
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Project Management Experience, Project Team Size, Project Duration and Project Value Size on the Relationship between Project Manager’s Leadership Roles and Project Team Effectiveness in Malaysia

Abstract: Many organizations are using project teams to achieve their organizational goals because they believe the importance and benefits of project teams. Project managers are advised to learn and demonstrate the leadership roles as proposed by Quinn (1988)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…The findings (Table 3) showed that overall, all the projects are managed using mostly the transformational leadership style (Project A = 2.86; Project B = 2.63; Project C = 2.12), followed by the transactional leadership style (Project A = 2.17; Project B = 1.87; Project C = 1.68). This finding supports past works that stipulate the preference of transformational leadership style over others for project delivery [43][44][45]. The projects scored least for a Laissez-faire amongst all the leadership styles tested.…”
Section: Leadership Styles Per Projectsupporting
confidence: 89%
“…The findings (Table 3) showed that overall, all the projects are managed using mostly the transformational leadership style (Project A = 2.86; Project B = 2.63; Project C = 2.12), followed by the transactional leadership style (Project A = 2.17; Project B = 1.87; Project C = 1.68). This finding supports past works that stipulate the preference of transformational leadership style over others for project delivery [43][44][45]. The projects scored least for a Laissez-faire amongst all the leadership styles tested.…”
Section: Leadership Styles Per Projectsupporting
confidence: 89%
“…Longer project durations also allow for broader organizational design to influence teams. For instance, in a field study including 201 project managers from Malaysia, Fung (2015) found that project duration moderated the relationship between project manager leadership and team effectiveness, such that leadership increased in importance as project duration increased.…”
Section: Task Designmentioning
confidence: 99%
“…This finding is consistent with the studies of Pinto (1986), Kerzner (1987), Pinto and Slevin (1989), Wateridge (1995), Belout (1998), Cooke-Davies (2002), and Muller and Turner (2005). Fung (2015) mentioned that team building and engagement could directly influence project performance outcomes. The extra effect that synergy would bring to the team is to create a new team culture that includes group norms, attitudes and practices which foster the achievement of project objectives (Philip, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness ought to be applied in various structures of an organization or business activities to gain positive outcomes (Petro and Gardiner, 2015). From the managerial perspective, a business is able to operate efficiently if the people are performing their required tasks effectively (Fung, 2015). The more consistent employees perform their tasks adequately with proper use of technology, communication skills, knowledge sharing, problem solving skills, organizational relationship and high impact resources, the higher the rate of effectiveness will be obtained (Petro and Gardiner, 2015).…”
Section: Introductionmentioning
confidence: 99%